Fatal Infection Caused by Chromobacterium violaceum: A Case Report from a Tertiary Care Hospital in Bangladesh - Sadia Sharmin; Aflatun Akter Jahan; S. M. Mostofa Kamal; Protim Sarker (Case Reports in Infectious Diseases)
Chromobacterium violaceum is a Gram-negative bacterium, found in tropical and subtropical regions. C. violaceum infection rarely occurs, but once occurs, it is associated with significant mortality due to severe systemic infection. Since the first human case from Malaysia in 1927, >150 cases of C. violaceum infection have been reported worldwide. We have described here a fatal case of C. violaceum infection in a tertiary care hospital in Dhaka, Bangladesh. To the best of our knowledge, this is the first case of C. violaceum infection in Bangladesh.